2017
DOI: 10.1016/j.ygyno.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Hospital readmission after ovarian cancer surgery: Are we measuring surgical quality?

Abstract: Objectives Readmission after surgery is a quality metric hypothesized to reflect the quality of care in the index hospitalization. We examined the link between readmissions and a surrogate of surgical quality -- major postoperative complication -- among ovarian cancer patients. Methods Patients who underwent surgery for ovarian cancer between 2012–2013 were identified from the National Surgical Quality Improvement Project (NSQIP). Major complications were defined as > grade 3 complications on the validated C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Additionally, these effects are most pronounced in patients undergoing aggressive cytoreductive efforts (6). Postoperative complications are known to be a major driver of early (30 day) postoperative readmissions and this increased rate of complications is likely a factor in the increased rate of readmission among patients receiving primary debulking surgery (16). If neoadjuvant chemotherapy is associated with decreased readmissions and non-inferior survival compared with primary debulking surgery, as demonstrated in large European randomized studies, then neoadjuvant chemotherapy is the preferred strategy for high value care.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these effects are most pronounced in patients undergoing aggressive cytoreductive efforts (6). Postoperative complications are known to be a major driver of early (30 day) postoperative readmissions and this increased rate of complications is likely a factor in the increased rate of readmission among patients receiving primary debulking surgery (16). If neoadjuvant chemotherapy is associated with decreased readmissions and non-inferior survival compared with primary debulking surgery, as demonstrated in large European randomized studies, then neoadjuvant chemotherapy is the preferred strategy for high value care.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reliability of this metric as a measure of quality in ovarian cancer surgery has been questioned. 47 Although we found vulvar reconstruction to be the most predictive variable for unplanned readmission, this metric is not necessarily an accurate predictor of surgical quality. As with a study of hospital readmission rates and quality in ovarian cancer surgery, readmissions may be related to postoperative complications or completely independent factors such as socioeconomic status and issues with coordination of care.…”
Section: Discussionmentioning
confidence: 62%
“…As with a study of hospital readmission rates and quality in ovarian cancer surgery, readmissions may be related to postoperative complications or completely independent factors such as socioeconomic status and issues with coordination of care. 47 Long-term data regarding overall survival and quality of life could help determine if the 30-day outcomes in this study are reliable measures of quality in vulvar surgery.…”
Section: Discussionmentioning
confidence: 96%
“…ovarian cancer. [7][8][9] There is a high burden associated with hospital readmissions for patients, insurance providers, and the healthcare system. We assessed patient, hospital, and operative characteristics to identify predictors of readmission so that care and payment models might be better optimized at index hospitalization.…”
Section: Patient and Hospital Characteristics Of Cohorts With And Wmentioning
confidence: 99%
“…Previous studies have found minimal correlation between rehospitalization rates and overall survival following debulking surgery but have been mostly limited to the initial 30 days following discharge from index hospitalization. [7][8][9][10] Although postoperative readmission does not appear to correlate with surgical quality for patients with ovarian cancer, it does represent additional burden on the patient and healthcare system in terms of resource utilization. This burden has been thoroughly characterized for the first 30 days postoperatively, but increased understanding of outcomes beyond the first 30 days could help to guide treatment and payment model decisions for this population.…”
Section: Introductionmentioning
confidence: 99%